2015
DOI: 10.1146/annurev-immunol-032713-120140
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antibody Repertoires: Development and Functional Role in Inhibiting Allergic Airway Disease

Abstract: In this review we discuss the effects of microbial exposure on the B cell repertoire. Neonatal exposure to conserved bacterial carbohydrates and phospholipids permanently reprograms the natural antibody repertoire directed toward these antigens by clonal expansion, alterations in clonal dominance, and increased serum antibody levels. These epitopes are present not only in bacterial cell walls, but also in common environmental allergens. Neonatal immunization with bacterial polysaccharide vaccines results in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 110 publications
4
89
0
Order By: Relevance
“…17 Paradoxically, these polysaccharide-reactive antibodies are often somatically hypermutated, which suggests that somatic hypermutation in B cells and subsequent production of affinity-matured antibodies does not always require TCR engagement. 36,37 We set out to characterize the sequence of these three β-WTA-reactive antibodies to better understand their evolution from germline sequences (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Paradoxically, these polysaccharide-reactive antibodies are often somatically hypermutated, which suggests that somatic hypermutation in B cells and subsequent production of affinity-matured antibodies does not always require TCR engagement. 36,37 We set out to characterize the sequence of these three β-WTA-reactive antibodies to better understand their evolution from germline sequences (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…An important component of immune defenses against bacteria is a repertoire of germline “natural antibodies” that have affinity for non-protein bacterial epitopes such as carbohydrates. 16,17 These antibodies are produced in the absence of T-cell stimulation early in the course of infection, with the best-characterized Gram-positive responses against cell wall epitopes such as poly-N-acetylglucosamine (PNAG) and capsular polysaccharide (CP) teichoic acids from Staphylococcus species 18,19 and Streptococcus pneumoniae . 20 In addition, CPs are an important component of several bacterial vaccines, 21 and opsonizing antibodies targeting polysaccharides have been investigated as therapeutic agents for Burkholderia dolosa 22 and S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…They showed that injection of α1-3 dextran permanently altered the repertoire of carbohydrate-reactive B cells when given within a short window after birth, but not later (summarized in (62)). This antigen is known to activate B-1 cells (63), and is expressed on Aspergillus fumigatus as well as house dust mites, While immunization did not change anti- α1-3 dextran serum IgM levels, it expanded the repertoire of polysaccharide-specific B cells and protected the mice from increased airway reactivity and signs of TH2-mediated airway disease (64).…”
Section: B-1 Cell Repertoire Selection and Maintenancementioning
confidence: 99%
“…Natural antibodies against carbohydrates are found in humans and other mammals. Their origin is a matter of debate, but exposure to microbial carbohydrates is believed to play a major role in their formation (123). Naturally acquired antiglycan antibodies vary Antibody analysis using glycan arrays for cancer research.…”
Section: Biomarkers and Vaccinesmentioning
confidence: 99%